Water-triggered frontal polymerization - Pujari, Narahari S.; Inamdar, Satish R.; Ponrathnam, Surendra; Kulkarni, Bhaskar D. (Macromolecular Rapid Communications, 2007)
A totally new mode of frontal polymerization (FP) of acrylamide is established which is triggered by the simple addition of a minute, specific volume of water. Experimental conditions under which this mode of polymerization yields linear and water-soluble polyacrylamide were carefully established, paving the way to synthesize commercially pertinent homo- and copolymers. A new redox couple was identified to circumvent the imidization and the ensuing gelation, hitherto associated with FP of acrylamide. Effects of reaction variables such as type and concentration of redox couple and volume of water on measurable parameters of FP such as front velocity, front temperature, shape of front and yield have been studied. Two types of redox couples are reported. Nonplanar frontal regime was observed in few redox couples. We could visually observe helical patterns with naked eyes, while layered patterns were observable under SEM. Additionally, micro-phase separation and heterogeneity in the polymer matrix was observed due to unreacted pockets of monomer which evolve via bulk mode. This nonlinear phenomenon is described.